Biodegradation of 1,2,3-Trichloropropane through Directed Evolution and Heterologous Expression of a Haloalkane Dehalogenase Gene - Bosma, Tjibbe (American Society for Microbiology, 2002)
Using a combined strategy of random mutagenesis of haloalkane dehalogenase and genetic engineering of a chloropropanol-utilizing bacterium, we constructed an organism that is capable of growth on 1,2,3-trichloropropane (TCP). This highly toxic and recalcitrant compound is a waste product generated from the manufacture of the industrial chemical epichlorohydrin. Attempts to select and enrich bacterial cultures that can degrade TCP from environmental samples have repeatedly been unsuccessful, prohibiting the development of a biological process for groundwater treatment. The critical step in the aerobic degradation of TCP is the initial dehalogenation to 2,3-dichloro-1-propanol. We used random mutagenesis and screening on eosin-methylene blue agar plates to improve the activity on TCP of the haloalkane dehalogenase from Rhodococcus sp. m15-3 (DhaA). A second-generation mutant containing two amino acid substitutions, Cys176Tyr and Tyr273Phe, was nearly eight times more efficient in dehalogenating TCP than wild-type dehalogenase. Molecular modeling of the mutant dehalogenase indicated that the Cys176Tyr mutation has a global effect on the active-site structure, allowing a more productive binding of TCP within the active site, which was further fine tuned by Tyr273Phe. The evolved haloalkane dehalogenase was expressed under control of a constitutive promoter in the 2,3-dichloro-1-propanol-utilizing bacterium Agrobacterium radiobacter AD1, and the resulting strain was able to utilize TCP as the sole carbon and energy source. These results demonstrated that directed evolution of a key catabolic enzyme and its subsequent recruitment by a suitable host organism can be used for the construction of bacteria for the degradation of a toxic and environmentally recalcitrant chemical.